824 UK CoPACK Study: Health Care Workers Knowledge and Confidence in Using Personal Protective Equipment (PPE) And Related Anxiety Levels During The COVID-19 Pandemic. (12th October 2021) - Ismael, S; Manoharan, G; Al-Kaisi, K; George, A; Abas, S; Al Musabi, M; Rao, P; Singh, R
Abstract: Aim: The COVID-19 pandemic has resulted in significant pressures on the NHS. Healthcare workers (HCWs) are at increased risk of infection. Personal protective equipment (PPE) lowers the risk of infection transmission. However, during the early phases of the pandemic, the information available regarding COVD-19 and the use of PPE has been unclear, with constantly changing guidelines. The aim of this study was to determine the knowledge and confidence about PPE usage among HCWs, in addition to measuring their anxiety levels during the COVID pandemic. Method: A validated questionnaire was distributed among HCWs in as many UK hospitals as possible, during April 2020. The questionnaire consisted of 13 questions regarding demographics, knowledge on PPE guidance, HCW training and confidence levels in PPE usage and finally anxiety levels measured using the GAD-7 psychometric tool. Results: 1055 responses were received. Nurses (49%), Healthcare Assistants (HCA - 20%), Doctors (17%), Physios (8%) and other (6%). 99% of respondents indicated they were familiar with PPE guidance, but only 1.6% answered all 3 questions on PPE guidance accurately. 86.4% of respondents received mask-fitting checks. 79.7% received donning-doffing training. Despite this, only 46.8% were confident on their familiarity with PPE. 32.5% felt that their hospital communication regarding PPE policy during COVID-19 pandemic was poor or very poor. 30% HCWs experienced severe anxiety. Conclusions: National guidance and local training on PPE usage during the COVID-19 pandemic has been unsatisfactory, leading to higher anxiety among HCWs. Improved information delivery and training are essential in preparation for the second wave and future pandemics.